Rootstocks for almond. Historical review, present situation and perspectives in Greece - Stylianidis D.C.; Syrgianidis G.D. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
The general situation of almond rootstocks in Greece is presented, as well as some research on this field at the Pomology Institute of Naoussa. Also reviewed are the most important problems related to rootstocks, mainly drought resistance and phytopathological problems.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)